The People's Bath and Sweet Waters Park - Acquisto, Luciana (School of Architecture, Planning and Geomatics, 2018)
The research document component of this dissertation concludes that Cape Town's sanitation crisis can in part be relieved by the implementation of consolidated sanitation infrastructure in wealthy areas, visited daily by thousands affected by the crisis. These wealthy areas are capable of maintaining and implementing these types of facilities due to rates ring-fencing. Furthermore, the document looked at historic precedent to demonstrate that this strategy has grounds and has acted as a sanitation crisis alleviation mechanism many times in history. The dissertation design focuses on both the sanitation and water crisis in Cape Town, and proposes to in part alleviate pressure locally from within the City Bowl by making use of the abundant quantity of water produced daily by the Camissa spring network coming of Table Mountain. The design uses this water to cater to the needs of people seeking ablution, swimming, and recreational outdoor facilities, from the rich to the poor, attempting to bring together folk from all walks of life in one mutually inclusive, water sensitive design.